The Doctrine of Wahdatul Wujud: The Issue of Contamination of the Study of Islamic Sufism with Greek Philosophy - Matussein Haji Jumat (Journal of Social Transformation and Regional Development, 2021)
This study discusses the doctrine of wahdatul wujud which sneaks into the discipline of the study of tasawwuf. This doctrine is said to be sourced from India and circulated to the archipelago by the ulemas Hamzah Shamsuddin Fansuri and as-Sumatrani and strengthened through scientific research thesis nowadays seems to part of the doctrine of Islamic scholarship. This situation prompts the author to study the errors of this doctrine in an effort to defend the purity of monotheism from the pollution done through tasawwuf. The study found that this doctrine uses the verses of mutasyabihat in the interpretation of the Qur’an to adapt to the will of wahdatul wujud which all lead to the incarnation of the essence of Allah Ta’ala in all beings that is an understanding that contradicts the belief in the nature of the twenty beliefs of Ahli Sunnah Wal Jamaah. Thus, the doctrine of wahdatul wujud is the pollution of aqeedah thinking which is actually not related to the discipline of the study of tasawwuf according to the teachings of Islam.